(untitled) (Revista Cocar, 2011)
" LOPES, Sonia de Castro. Oficina de Mestres: história, memória e silêncio sobre a escola de professores do Instituto de Educação do Rio de Janeiro (1932-1939). Rio de Janeiro: DP&A Faperj, 2006 A Masterâ€™s Dream: Teachers Workshop "LOPES, Sonia de Castro. Masters Workshop: history, memory and silence about the school of teachers of the Institute of Education of Rio de Janeiro (1932-1939). Rio de Janeiro: DP & A Faperj, 2006